Study Of Dosha Dushya Sammurchana In Indralupta And Its Management With Bhallataka And Madhu W.S.R. To Alopecia Areata - Gupta, Vikas; Sodhi, Danisha; Panjgotra, Sakshi (International Research Journal of Ayurveda & Yoga, 2021)
Indralupta is a skin ailment that affects all the hair-bearing skin including beard and scalp. Patients who are suffering from Indralupta experiences loss of hair which is not like the usual hair loss but rather tufts of hair which tend to fall out over a short period of time. According to the science of Ayurveda, out of three vital Doshas of our body, Vata and Pitta get localized in the hair pores in the scalp region in aggravated condition. This condition obstructs micro-channels (Sleshma and Shonita)to supply nutrients to the hair follicle, which results in falling of tufts of hair in that particular region and also preventing further regrowth of hair that leaves a bald patch. Bhallataka is identified botanically as Semecarpus anacardium Linn.f. comes under the family Anacardiaceae. It is commonly known as Indian marking nut and used extensively in the system of Ayurveda to cure many diseases like Arshas (piles), Arbuda (cancer) etc. Bhallataka is mentioned under Upavisha group in Ayurvedic classics and it is described as a poisonous medicinal plant in Drugs and Cosmetics Act (India), 1940. Bhallataka should be used after proper shodhana (purification/processing). Different shodhana methods are mentioned in the Ayurvedic literature. In this study Bhallatak and Honey have been used to provide therapeutic relief to the patients of Indralupta